Biosorption of Ciprofloxacin (CIP) using the Waste of Extraction Process of Microalgae: The Equilibrium Isotherm and Kinetic Study - Al-Mashhadani, Enass S. M.; Al-Mashhadani, Mahmood K. H.; Al-Maari, Mohammed Abobakr (Iraqi Journal of Chemical and Petroleum Engineering, 2023)
Scientists are investigating the efficacy of different biosorbents for promoting economic and environmental viability in purifying contaminants. Among the primary by-products of biodiesel production is waste microalgae biomass, which has the potential to be used as a cheap biosorbent for the treatment of pollution. In the present study, the biomass left over after extracting the chlorella vulgaris was used to test the potential biosorption of CIP from simulated aqueous solutions. Bisorbent’s ability was characterized using Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (EDX). Analysis with a Fourier Transform Infrared Spectrometer revealed that CIP biosorption occurred mainly at biomass sites containing carboxyl and amino groups. The equilibrium isotherm data and biosorption kinetics were addressed in the present study. The biosorption data match the Langmuir isotherm model, and the maximal biosorption capacity was determined to be 7.56 mg/g. While The pseudo-second-order model accurately described the biosorption kinetic data. Biosorbent regeneration was also studied using two different sodium hydroxide concentrations, the results showing that after desorption, the biosorption capacity decreased from 5.2 to 3.74 and 1.77 (mg/g) using 0.1NaOH and 0.5NaOH, respectively.